2002
DOI: 10.1067/mhn.2002.123104
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Proto‐Oncogene eIF4E in Inflammation of the Oral Cavity

Abstract: 4E is not significantly elevated in inflammation of the oral cavity thus fulfilling one of the criteria that biomarkers require to be useful in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(55 reference statements)
2
10
0
Order By: Relevance
“…Among them 6 identified proteins were unique to OSCC including ladinin 1, eukaryotic initiation factor 4A-I, cathepsin D, cofilin-1, laminin subunit beta-3 and protein S100-A9 and 3 were unique to adjacent, histologically unaltered tissues including mimecan, suprabasin and cystatin-A. These findings are in line with previous studies which showed increased expression of the protease cathepsin D [32], eukaryotic initiation factor 4A-I [35], cofilin -1 [36] and S100A9 protein [37] in OSCC which was correlated with progression and invasion of tumor cells. In addition, decreased expression of small leucine rich proteoglycan mimecan was previously reported in the oesophageal squamous cell carcinoma [38].…”
Section: Discussionsupporting
confidence: 89%
“…Among them 6 identified proteins were unique to OSCC including ladinin 1, eukaryotic initiation factor 4A-I, cathepsin D, cofilin-1, laminin subunit beta-3 and protein S100-A9 and 3 were unique to adjacent, histologically unaltered tissues including mimecan, suprabasin and cystatin-A. These findings are in line with previous studies which showed increased expression of the protease cathepsin D [32], eukaryotic initiation factor 4A-I [35], cofilin -1 [36] and S100A9 protein [37] in OSCC which was correlated with progression and invasion of tumor cells. In addition, decreased expression of small leucine rich proteoglycan mimecan was previously reported in the oesophageal squamous cell carcinoma [38].…”
Section: Discussionsupporting
confidence: 89%
“…eIF4E is overexpressed in many epithelial cell cancers, including breast [812], colon [13, 14], bladder [1519], cervix [20, 21], lung [2224], and squamous cell carcinoma of the head and neck [2532]. Some studies report that eIF4E is overexpressed in almost 100% of tumors of the breast, head and neck, and colon [8, 27, 32].…”
Section: Generalized Role For Eif4e In Cancermentioning
confidence: 99%
“…Benign tumors only had moderate evidence for gene amplification, while malignant tumors had a 4–15 fold level of amplification [43]. eIF4E protein levels were elevated in premalignant lesions in the larynx, but to a lesser extent than observed in HNSCC [25]. These studies suggest that progression to the malignant phenotype paralleled eIF4E gene amplification and overexpression [43].…”
Section: Dysregulation Of Eif4e In Hnsccmentioning
confidence: 99%
“…However, when comparing MSI with LOH and p53 mutation assays, MSI is less frequent in head and neck SCC. EIF4E has been shown to be elevated in 100% of head and neck SCC [58]. Chandy et al [45] demonstrated the presence of EIF4E in 42% in surgical margins in patients with SCC.…”
Section: P53 and Microsatellitesmentioning
confidence: 98%
“…Application of the modified FASAY identified one patient with clinically and histological normal mucosa harbouring a p53 mutation confirming a role of genetic aberrations in carcinogenesis. Others have investigated [53][54][55][56][57] microsatellite alterations and eIf4E [58] overexpression and provided a link between positive surgical margins and tumour recurrence. Microsatellites are polymorphic loci present in nuclear DNA and organellar DNA that consist of repeating units of 1-4 base pairs in length.…”
Section: P53 and Microsatellitesmentioning
confidence: 99%